Domestic animal proteomics in the 21st century: a global retrospective and viewpoint analysis - Almeida, André M. (2021)
Animal production and health are of significant economic importance, particularly regarding the world food supply. Animal and veterinary sciences have evolved immensely in the past six decades, particularly in genetics, nutrition, housing, management and health. To address major challenges such as those posed by climate change or metabolic disorders, it is of utmost importance to use state-of-the-art research tools. Proteomics and the other post-genomic tools (transcriptomics or metabolomics) are among them. Proteomics has experienced a considerable development over the last decades. This brought developments to different scientific fields. The use and adoption of proteomics tools in animal and veterinary sciences has some limitations (database availability or access to proteomics platforms and funding). As a result, proteomics’ use by animal science researchers varies across the globe. In this viewpoint article, we focus on the developments of domestic animal proteomics over the last decade in different regions of the globe and how the researhers have coped with such challenges. In the second part of the article, we provide examples of funding, educational and laboratory establishment initiatives designed to foster the development of (animal-based) proteomics. International scientific collaboration is a definitive and key feature in the development and advancement of domestic animal proteomics